EVALUASI WAKTU DAN BIAYA MENGGUNAKAN METODE EARNED VALUE ANALYSIS PADA PROYEK PEMBANGUNAN PUSKESMAS TALUN Kab. BLITAR - Reza Rahmattullah; Masca Indra Triana (Racic : Rab Construction Research, 2024)
The Earned Value approach is employed to meticulously track project time and expenses, facilitating early identification of performance issues. Specifically, the construction project for the community health center in Talun, Blitar, encountered variations during the 11th to 13th weeks. Upon doing an analysis in the 13th week, it was discovered that the Schedule Variance (SV) amounted to IDR. -165,313,862.5, suggesting that the actual employment (BCWP) was lower than the anticipated employment (BCWS). The Cost Variance (CV) is Rp. 286,761,471.2, showing that the cost is less than the value of the work accomplished. The SPI (Schedule Performance Index) for week 13 was 0.7, signifying a significant delay in the execution of the project. The Consumer Price Index (CPI) recorded a value of 3.64 in week 13, suggesting that spending efficiency fell short of the budgeted target.